If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 1 = 6x + 4 Reorder the terms: 1 + 7x = 6x + 4 Reorder the terms: 1 + 7x = 4 + 6x Solving 1 + 7x = 4 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 1 + 7x + -6x = 4 + 6x + -6x Combine like terms: 7x + -6x = 1x 1 + 1x = 4 + 6x + -6x Combine like terms: 6x + -6x = 0 1 + 1x = 4 + 0 1 + 1x = 4 Add '-1' to each side of the equation. 1 + -1 + 1x = 4 + -1 Combine like terms: 1 + -1 = 0 0 + 1x = 4 + -1 1x = 4 + -1 Combine like terms: 4 + -1 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| 6m^2n/24mn | | 10-5x=(20-10x)1/2 | | 2x=27-1 | | h(x)=7x^2-3 | | 4cos(pi/4) | | 6x^3-9x^2-6x=0 | | r(x)=3(1.4)x | | c=2pi*5 | | 44-12w=-3 | | 0=12w-47 | | (6x-4)-(2x+8)= | | 20=12+2x | | f(-2)=4x^2-8x+3 | | -x+3x=10 | | 40x+8x=720 | | 3x-9x^2=10 | | h(x)=1/x | | Xsquared=4000 | | 20u^2-88u+32=0 | | 1=2x+4d-d+7i | | x^3-4x=21 | | log[4](36)+log[4](2x+3)=log[4](8x-14) | | 2log[4](6)+log[4](2x+3)=log[4](8x-14) | | (2x+1)(2x+3)=99 | | 0=2u-20 | | 5x/6=11/4=17/3 | | 6x^2-12x-x=0 | | 6=3n/5 | | 9=3(v+2) | | (6-i)-(9+7i)= | | 34=2w+10 | | f(15)=2.479g |